Numerical studies on engineered smoke control and fire suppression system for underground vehicular tunnel - Lee, Jia Sheng (2018)
Due to scarcity of land area to sustain the population expansion and economic growth, the use of underground space has been actively explored. Following the extensive rail network underground currently, it is expected that the underground vehicular tunnel (VT) will be the next trend to explore underground usage for transportation system. Nevertheless, compared to its above-ground counterpart, the development of underground VT which is relatively new, may be lacking established building and engineering codes and regulations to comply with. Hence, this project aims to design an Engineered Smoke Control (ESC) and fire suppression system for such VT, with a minimum requirement to satisfy the tenability criteria as specified in Singapore Fire Safety Engineering Guidelines (SFEG) 2015. This project conducts multiple optimisation studies on the ESC system to improve the effectiveness and efficiency of the system. Based on the results, it was found that under the constraint of total available volumetric exhaust rate, the use of shorter ESC activation zone length and zone redistribution activation method were able to significantly improve the performance of ESC system. Meanwhile, a more cost-efficient design can be achieved by increasing the exhaust duct separation distance such that the overall length of the ducting system will be decreased. In view of various constraints imposed for the design of ESC system, the implementation of ESC system with 45 m zone length, zone redistribution activation, and duct separation of 5.4 m is recommended. A new system which simultaneously utilizes the WMC is also proposed as a feasible strategy to complement and reduce the heavy reliance on the ESC system to control the smoke spread. Lastly, based on the existing constraints of the simulation model and the requirement by the project, auto jet system has shown a considerable advantage over the deluge water mist system, as the fire suppression system for VT. In this project, all the assessments on the fire scenarios were done numerically using Fire Dynamics Simulator (FDS). PyroSim, a graphical user interface of the FDS was also used to pre-process the simulations and post-process the simulation results.